2018
DOI: 10.1002/slct.201800252
|View full text |Cite
|
Sign up to set email alerts
|

Multicoloured Thiophene Based AIEgens: Single Crystal Structure Elucidation, Spectral Behaviour and DFT Studies

Abstract: A series of Schiff base thiophene derivatives, D1 to D9, which exhibits a phenomenon of aggregation‐induced emission enhancement (AIEE) have been synthesised and characterized by standard spectroscopic techniques. Multicoloured emission enhancement has been achieved just by introduction of electron donating and withdrawing substituent on the thiophene moiety. Few of the molecules in the series exhibited enhanced fluorescence emission intensity in solvent mixture in comparison with that observed in pure solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…So far, Trivedi et al have proven that the unfavorable π−π stacking can be prevented by increasing the distance between interacting π systems in the crystal. 20 Recently, it has been experimentally found that both anions and cations can form a noncovalent interaction with the π system to replace the unfavorable π−π interaction. 21,22 The pyridine cation−π interaction was used to generate luminescence responses in solution as early as 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, Trivedi et al have proven that the unfavorable π−π stacking can be prevented by increasing the distance between interacting π systems in the crystal. 20 Recently, it has been experimentally found that both anions and cations can form a noncovalent interaction with the π system to replace the unfavorable π−π interaction. 21,22 The pyridine cation−π interaction was used to generate luminescence responses in solution as early as 2011.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the unfavorable π–π interaction in the solid state makes the organic luminescent systems in the excited state undergo a decay in energy, which leads to a decrease in the luminescence efficiency. , Obviously, the search for an alternative intermolecular interaction that can avoid harmful intermolecular π–π interactions will facilitate one to design AIE systems with excellent luminescence properties. So far, Trivedi et al have proven that the unfavorable π–π stacking can be prevented by increasing the distance between interacting π systems in the crystal . Recently, it has been experimentally found that both anions and cations can form a noncovalent interaction with the π system to replace the unfavorable π–π interaction. , The pyridine cation−π interaction was used to generate luminescence responses in solution as early as 2011 .…”
Section: Introductionmentioning
confidence: 99%